Pathogenesis and Clinical Relevance of Candida Biofilms in Vulvovaginal Candidiasis - Rodríguez-Cerdeira, Carmen; Martínez-Herrera, Erick; Carnero-Gregorio, Miguel; López-Barcenas, Adriana; Fabbrocini, Gabriella; Fida, Monika; El-Samahy, May; González-Cespón, José Luís (Frontiers in Microbiology, 2020)
The ability of Candida spp. to form biofilms is crucial for its pathogenicity, and thus, it should be considered an important virulence factor in vulvovaginal candidiasis (VVC) and recurrent VVC (RVVC). Its ability to generate biofilms is multifactorial and is generally believed to depend on the site of infection, species and strain involved, and the microenvironment in which the infection develops. Therefore, both cell surface proteins, such as Hwp1, Als1, and Als2, and the cell wall-related protein, Sun41, play a critical role in the adhesion and virulence of the biofilm. Immunological and pharmacological approaches have identified the NLRP3 inflammasome as a crucial molecular factor contributing to host immunopathology. In this context, we have earlier shown that Candida albicans associated with hyphae-secreted aspartyl proteinases (specifically SAP4-6) contribute to the immunopathology of the disease. Transcriptome profiling has revealed that non-coding transcripts regulate protein synthesis post-transcriptionally, which is important for the growth of Candida spp. Other studies have employed RNA sequencing to identify differences in the 1,245 Candida genes involved in surface and invasive cellular metabolism regulation. In vitro systems allow the simultaneous processing of a large number of samples, making them an ideal screening technique for estimating various physicochemical parameters, testing the activity of antimicrobial agents, and analysing genes involved in biofilm formation and regulation (in situ) in specific strains. Murine VVC models are used to study C. albicans infection, especially in trials of novel treatments and to understand the cause(s) for resistance to conventional therapeutics. This review on the clinical relevance of Candida biofilms in VVC focuses on important advances in its genomics, transcriptomics, and proteomics. Moreover, recent experiments on the influence of biofilm formation on VVC or RVVC pathogenesis in laboratory animals have been discussed. A clear elucidation of one of the pathogenesis mechanisms employed by Candida biofilms in vulvovaginal candidiasis and its applications in clinical practice represents the most significant contribution of this manuscript.